Auditoría informática a la gestión de las Tic´S A la empresa Markglob de la ciudad de Machala. - Galvez Freire, Maritza Anabel (My University, 2019)
In the global context of the business field, business strategies, commercial advice and innovation through the ICTs are dynamized. MARKGLOB is an entity in charge of planning, advertising and optimizing the development of SMEs in the city of Machala through strategies of the market. The management of new communication and information technologies, in a compulsory way, requires knowledge in digital systems, cloud computing platforms / services administered by computerized means; that in spite of their qualities also derogate risks that must be taken care of in all contemporary organization, due to the great demand of data in real time and in continuous form. The purpose of this study is to describe the techniques, procedures or implements used by the MARKGLOB company to manage their ICTs when providing their services to society; As a method, the principles of computer audit, systematic analysis and documented research are used.
En el contexto global del campo empresarial, se dinamizan las estrategias de negocios, asesoría comercial e innovación a través de las TIC`s la marca MARKGLOB es una entidad encargada de planear, publicitar y optimizar el desarrollo de Pymes en la ciudad de Machala mediante estrategias de mercado. La gestión de las nuevas tecnologías de comunicación e información, en forma obligatoria demanda conocimientos en sistemas digitales, plataformas/servicios cloud computing administrados por medios informáticos; que pese a sus cualidades también derogan riesgos que deben ser atendidos en toda organización contemporánea, debido a la gran demanda de datos en tiempo real y en forma continua. El presente estudio tiene por objeto describir las técnicas, procedimientos o implementos que emplea la empresa MARKGLOB para gestionar sus TIC`s a la hora de prestar sus servicios a la sociedad; como método se utilizan los principios de la auditoria informática, análisis sistemático e investigación documentada.
Keywords: GESTIÓN; TIC`S; AUDITORIA INFORMÁTICA; MARKGLOB